A 40-year-old Woman with Hypercalcemia Crisis Caused by Bone Metastasis in Stage IV Breast Cancer - Wiharjo Hadisuwarno; Merlyna Savitri; Ami Ashariati; S. Ugroseno Yudho Bintoro; M. Noor Diansyah; Putu Niken Ayu Amrita; Pradana Zaky Romadhon (Biomolecular and Health Science Journal, 2021)
Breast cancer is still global burden especially for woman with 2.3 million cases every year dan 15% mortality among cancer diseases. In developing countries, most of the cases are diagnosed at terminal stage when metastasis already found. Bone metastasis is the highest among other metastasis sites such as: lung, liver and brain. Bone metastasis will cause hypercalcemia and bone pain as complications.  Both will gradually decrease patient’s quality of life. Comprehensive and holistic management for these complications will reduce deterioration and hopefully increase patient’s quality of life even they were at terminal stage. We describe a 40-year-old woman who got hypercalcemia crisis. Hypercalcemia usually manifest as a consequence of other diseases. Epidemiologically, majority come from metastasis, but can be other diseases, such as multiple myeloma. Interestingly, during medical investigation through her medical history, and physical examination, and laboratory examinations, we conclude that her hypercalcemia crisis was caused by bone metastasis from breast cancer.